Diversity, Abundance, Spatial Variation, and Human Impacts in Marine Meiobenthic Nematode and Copepod Communities at Casey Station, East Antarctica - Stark, Jonathan S.; Mohammad, Mahadi; McMinn, Andrew; Ingels, Jeroen (Frontiers in Marine Science, 2020)
The composition, spatial structure, diversity and abundance of Antarctic nematode and copepod meiobenthic communities was examined in shallow (5–25 m) marine coastal sediments at Casey Station, East Antarctica. The sampling design incorporated spatial scales ranging from 10 meters to kilometers and included testing for human impacts by comparing polluted (metal and hydrocarbon contaminated sediments adjacent to old waste disposal sites) and control areas. A total of 38 nematode genera and 20 copepod families were recorded with nematodes being dominant, comprising up to 95% of the total abundance. Variation was greatest at the largest scale (km’s) but each location had distinct assemblages. At smaller scales there were different patterns of variation for nematodes and copepods. There were significant differences between communities at control and impacted locations. Community patterns had strong correlations with concentrations of metals introduced by human activity in sediments as well as sediment grain size and total organic content. Given the strong association with environmental patterns, particularly those associated with human impacts, we provide further evidence that meiofauna are very useful indicators of anthropogenic environmental changes in Antarctica.